Removal of β-carotene from palm oil mill effluent by molecular imprinted polymer based on cyclodextrin- co-vinylcarbazole and cyclodextrin-co-hydroxyethyl methacrylate - Altogbia, Warda Mohamed Ali (2019)
Palm oil mill effluent (POME) the most significant pollutant in the form of wastewater, if not managed properly, it could have negative effects on the environment include the emission of biogas and water pollution which comes from discharging the brownish tick POME to the water bodies. Discharge of dark brownish colored of POME into water bodies will prevent the growth of aqua organism by reducing the penetration of sunlight and affect the photosynthetic activity. Such concern provides incentive to remove color from POME. In recent years, molecular imprinted polymers (MIP) attracted wide attention in treatment of wastewater due to their capability for molecular recognition, easiness of preparation, stability and cost-effective production. In this research, MIPs were synthesized by bulk polymerization method using β- cyclodextrin (β-CD) as monomer, 9-vinylcarbazole (9VC) and 2-hydroxylethyl methacrylate (HEMA) as co monomers, Toluene2,4-diisocyanate (TDI) as crosslinker, N,N-Dimethylformamide (DMF) as porogen solvent and Benzoyl peroxide (BPO) as initiator. The temperature used during polymerization process was 70oC. The obtained MIP was crushed, sieved and washed to remove the template. Increase the ratio of monomer to cross-linker lead to increase the yield weight of the MIPs. The optimal ratio of monomer to cross-linker was 1:5:58 and 1:17:58 for MIP-β-CD-9VC and MIP-β-CD-HEMA respectively. FTIR result showed that MIP (Molecular Imprinted Polymer) and NIP (Non-Imprinted Polymer) have similar characteristic peak with different peaks intensity, indicating the similarity in the backbone structure of polymerization. TGA result displayed high thermal stability with final decomposition at 320oC and 307oC for MIP-β-CD-9VC and MIP-β-CD-HEMA respectively. FESEM shows that MIP has rough surface while NIP possess densely packed particles with smooth surface. From BET result, the surface area for MIP-β- CD-9VC is higher than NIP-β-CD-9VC, while the surface area for MIP-β-CD-HEMA is smaller compared with NIP-β-CD-HEMA. The pH study shows that sorption of β-carotene increased with decreasing the pH of POME and the maximum sorption capacities achieved at pH 2 were 10 μg/g and 8 μg/g for MIP-β-CD-9VC and MIP-β- CD-HEMA, respectively. Also, the sorption of β-carotene increased with increasing the dosage of MIP, and the maximum sorption achieved by using 500 mg of MIP. Both MIP-β-CD-9VC and MIP-β-CD-HEMA followed Freundlich isotherm with R2=0.9688 and R2=0.9817 respectively. Besides that, the sorption of β-carotene by MIPs is fast within few minutes and both MIP-β-CD-9VC and MIP-β-CD HEMA followed the pseudo second order with R2=0.9999. The reusability study for MIP-β- CD-9VC and MIP-β-CD-HEMA were tested five times and no significant loss in sorption capacity. However, MIP-β-CD-HEMA showed higher reusability compared with MIP-β-CD-9VC. A new type of molecular imprinted polymer as a sorbents for removal of β- carotene from palm oil mill effluent (POME) was successfully synthesized. The synthesized MIP-β-CD-9VC and MIP-β-CD-HEMA showed several characteristic such as high thermal stability, fast sorption kinetic and good reusability. Thus, MIP- β-CD-9VC and MIP-β-CD-HEMA can be potentially used as a sorbents for the removal of β-carotene from palm oil mill effluent (POME).